Approximate calculation of static mass analyzers based on two-dimensional fields - Spivak-Lavrov И.Ф.; Amantayeva А.Ш.; Baisanov О.А.; Shugaeva Т.Ж. (Recent Contributions to Physics, 2024)
The concurrent utilization of electric and magnetic fields in static mass analyzers proves highly effective in sparticle separation solely based on their masses, thereby ensuring remarkable analytical capabilities. High-resolution mass analyzers employ an achromatizing electrostatic system to precisely focus ion radiation by energy. Devices featuring zero energy dispersion are created through the collaborative action of electric achromatizing systems and the magnetic field within the analyzer, resulting in ion separation based solely on mass. Expanding the ion beam prior to its magnetic field exposure enhances the overall quality of static mass analyzers. This article delves into a static mass analyzer with dual ion beam focusing, elucidating the ion acceleration and deceleration processes at electrode boundaries, their focalization via a transaxial lens, and the impact of the electrostatic prism’s refractive surface on the mass analyzer’s "quality" parameter. Additionally, the transition from a sector homogeneous magnetic field to the fields generated by a two-dimensional magnetic prism and a three-electrode transaxial focusing lens is explored to augment the mass analyzer’s linear dispersion. To refine ion beam focus pre-magnetic field entry, the proposed adoption of a two-dimensional electrostatic prism promises heightened linear dispersion in the mass analyzer while expanding the beam pre-magnetic field entry. This study also examines the impact of a two-dimensional electric prism on the charged particle beam, presenting an approximate expression for its angular energy dispersion. It is demonstrated that a prism-based mass analyzer integrating two-dimensional electric and magnetic prisms enables energy-focused operations alongside enhanced linear dispersion and reduced linear dimensions.